Cost-effectiveness analysis comparing intensity-modulated radiotherapy with conformational radiotherapy (3D-RT) for prostate cancer in the brazilian health system - Viani,Gustavo Arruda (2021)
SUMMARY OBJECTIVE: The intensity-modulated radiotherapy (IMRT) has been established as the standard external-beam radiation technique to treat prostate cancer in several countries. In Brazil, the public health system and the National Health Agency do not reimburse its utilization. This study compared the cost-effectiveness of IMRT and tridimensional radiotherapy (3D-RT) from a payer’s perspective. METHODS: We built a Markov model to delineate the health states after treatment with IMRT and 3D-RT. The treatment-related toxicity data were extracted from the literature. The sensitivity analyses were performed over potential parameters. RESULTS: The incremental cost of IMRT was R$ 5,553.78. At a time horizon of 5 years, the quality-adjusted life expectancy after IMRT was higher than 3D-RT. The incremental cost-effectiveness ratio (ICER) of IMRT over 3D-RT was R$-296,74/quality-adjusted life year (QALY). Therefore, IMRT was the dominant strategy, which depended on the value of interventional procedures for severe toxicity and the difference between IMRT and 3D-RT reimbursement. The IMRT was still most likely to be cost-effective at a willingness-to-pay R$ 100,000/QALY, with a net monetary benefit (NMB) superior to 3D-RT after R$ 50,000.00, resulting in a difference of R$220.000,00 after 5 years. CONCLUSIONS: IMRT generated more values than 3D-RT for external-beam treatment. Given its potential to reduce late toxicity with hypofractionation, these data reinforce its incorporation to treat prostate cancer in the Brazilian health system from a payer’s perspective.